The Mediating Role of Attitude in Influencig Consumer Purchase Intention Towards Online Apparel Shopping in Malaysia - Selvi @ Kausiliha, Vijayan (2020)
Online apparel shopping has gained an immense share in Malaysia's e-commerce market. Despite being one of the top products online, the online apparel purchase intention is not well explored and a minimally researched topic among academicians. Given the potential of this segment, a holistic and integrated framework remain absent, which warrants the goal of this thesis. With Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB) as a baseline model, the conceptual framework was extended with attitude as the mediator together with seven variables (perceived risk, web experience, pricing, utilitarian shopping orientation, hedonic shopping orientation, convenience and products and service attributes) to study on the online apparel purchase intention. Specifically, this study pursued to develop a framework that represents the factors influencing consumers' purchase intention and examine the role of attitude as mediator. Based on purposive sampling via Facebook advertising, a total of 314 responses were garnered through a self-administered questionnaire from online shoppers in Malaysia. Through Partial Least Squares – Structural Equation Modelling (PLS-SEM), the results revealed that 17 out of 22 hypotheses tested are supported. The model explains a 74 percent variance in attitude and 91 percent variance in purchase intention. The study has established a direct relationship with perceived risk, web experience, pricing, utilitarian shopping orientation, hedonic shopping orientation, and products and service attributes towards attitude. Besides, the study has confirmed a direct relationship with pricing, utilitarian shopping orientation, hedonic shopping orientation, convenience towards online apparel purchase intention. The study has also confirmed the mediating effect with all independent variables except convenience, thus supporting the hypothesis as the mediating variable. Academically, the integrated framework contributes to marketing and online apparel literature by combining TAM, TPB, attitude as the mediator, and other variables in the Malaysian context. These novel findings provide an understanding of consumers' purchase intention and guidance to online retailers and marketers in articulating their marketing strategies to persuade favourable intention towards online apparel.